CONFIRMATORY FACTOR ANALYSIS UNTUK MENGUKUR PERTUMBUHAN PENDUDUK DI KABUPATEN BOJONEGORO - Moch Nur Faizin; Alif Yuanita Kartini (Journal of Mathematics Education and Science, 2021)
Population growth is closely related to the addition and or reduction of the population in a specific area. Many factors influence population growth in an area, including births, deaths, and population movements. The development of the population of Bojonegoro Regency until 2020 has increased every year. The population development in Bojonegoro Regency has increased by 0.96 percent, which is thought to be caused by births, migration, and economic growth. In this study, to measure population growth in Bojonegoro Regency, this study conducted confirmation or testing to determine how well the measured variables represented the factors formed using the confirmatory factor analysis (CFA) method. The results showed that the characteristics of population growth in the Bojonegoro Regency were influenced by three latent variables, including fertility, mortality, and migration. In contrast, the most dominant variables in influencing population growth were total births, live birth rates, female child ratio, and life expectancy: infant mortality rates, under-five mortality rates, out-migration, and gross migration. Abstrak Pertumbuhan penduduk erat kaitanya dengan penambahan dan atau pengurangan jumlah penduduk di suatu wilayah tertentu. Banyak factor yang mempengaruhi pertumbuhan penduduk di suatu wilayah diantaranya kelahiran, kematian dan perpindahan penduduk. Perkembangan jumlah penduduk Kabupaten Bojonegoro hingga tahun 2020 mengalami kenaikan setiap tahun. Perkembangan penduduk di Kabupaten Bojonegoro mengalami pertambahan sebesar 0,96 persen yang diduga disebabkan oleh kelahiran, migrasi dan pertumbuhan ekonomi. Untuk mengukur pertumbuhan penduduk di Kabupaten Bojonegoro, pada penelitian ini dilakukan konfirmasi atau pengujian untuk mengetahui seberapa baik variabel yang telah diukur dapat mewakili faktor yang terbentuk menggunakan metode confirmatory factor analysis (CFA). Hasil penelitian menunjukkan bahwa pada karakteristik pertumbuhan penduduk di Kabupaten Bojonegoro dipengaruhi oleh tiga variabel laten diantaranya yaitu fertilitas, mortalitas, dan migrasi, sementara variabel yang paling dominan dalam mempengaruhi pertumbuhan penduduk adalah jumlah kelahiran total, angka lahir hidup, rasio anak wanita, angka harapan hidup, angka kematian bayi, angka angka kematian balita, migrasi keluar, dan migrasi bruto.